Semantics Analysis to Denotative and Connotative Meaning on DPR IAN’s Scaredy Cat - Apsari Eka Putri; Otong Setiawan Djuharie (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study investigates the meanings associated with the song “Scaredy Cat” by Ian DPR, focusing on connotative and denotative aspects through a semantic perspective. Using qualitative research methods, this work builds on existing research related to figurative language. The findings highlight the complex interaction between the song's literal meaning and its deeper emotional implications, which collectively enhance its impact. Denotative aspects provide a clear understanding of the songwriter's experience, while connotative elements invite deeper engagement with themes of fear, anxiety, and vulnerability. This research reveals that figurative language, such as metaphors and imagery, contributes to the layered interpretation of songs. This complexity not only strengthens the emotional bond between the artist and the audience but also encourages listeners to reflect on their own feelings and experiences. The importance of language in music as a means of expressing human emotions is emphasized. By combining empathetic language and figurative language, songwriters can create a sense of release and emotional connection. The results align with previous research on the importance of figurative language in enhancing lyrical meaning and emotional resonance. Further research is recommended to explore the relationship between semantics and emotional expression across various music genres.